DAKWAH PLURALIS - A Syarifudin (Wardah, 2013)
The development Dakwah from time to time is quite dynamic . This is evident from the characteristics of the preachers , methods and media are always dynamically from one state to the next state . In addition , the development of thought patterns and situations mad'u times are demanding a change as if the force of thinkers / observers propaganda that this process can still take place and is able to maintain the balance of the course of life and human life . The problem that arises then is that social reality is happening in the community are not always stable and in line ( receiving ) process that occurs in the conventional propaganda . Not to mention , the rampant crisis of confidence due to the many konfrontal behavior carried out by a group of people who call themselves Muslims . Again, the face of the Institute of Islamic tarnished by these phenomena . Naturally, if there is Islamo phobia in certain communities who do not know Islam further. That is , the need for grain - grain Islam should rahmatan lil lamin , touching all levels of society , not the propaganda that discredit certain groups let alone to make them running scared because of improper packaging dakwah . This article attempts to outline the concept of dakwah pluralis as a dakwah package the rahmatan lil alamin.